UNBALANCED NUTRITION AS A FACTOR CAUSING DISRUPTIONS IN THE MENSTRUAL CYCLE AND OVARIAN FUNCTION IN YOUNG WOMEN INVOLVED IN BODYBUILDING - Safronova M.Y. ,; Tambovtseva R.V. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the relationship between nutritional deficiencies in female athletes specializing in bodybuilding and disorders of their ovarian-menstrual cycle (OMC). Methods and structure of the study. A rational method for reducing caloric intake by reducing fat intake was developed and a survey of girls specializing in bodybuilding was conducted. Results and conclusions. It was found that disorders (absence) of the OMC mainly occur due to a decrease in carbohydrates and fats to a critical level. The worst effect on the ovarian-menstrual cycle is a decrease in the percentage of fat in the diet to 10-15%. Those girls who maintained their OMC followed a diet containing 30-35% fat.